Teaching teachers: Approaches in improving quality of education - Saleh, I.; Khine, Myint Swe (Nova Science Publishers, Inc., 2011)
Teacher education plays a vital role in educating our future teacher-which in turn educates our children in today's information age and knowledge-based economy. Simply having knowledge is not enough; students equipped with having the necessary skills to apply knowledge in real life is more important. If any nation is in the process of improving education, it is imperative that it looks closely at how it organizes its teacher education program. This new book discusses the future of teacher education and presents thought-provoking ideas, innovative approaches, systemic explorations, exemplary and promising efforts and future-oriented scenarios in framing teacher education. © 2011 by Nova Science Publishers, Inc. All rights reserved.